Soil fungal community structure and ecological functions in fairy rings of Leucocalocybe mongolica in Bayanbulak grassland - Wang, Senyuan; Wang, Xingzhe; Xu, Jiajia; Na, Rimai; Wang, Yanan; Wei, Jie; Li, Fahu; Bao, Qiuli (Frontiers in Microbiology, 2025)
Leucocalocybe mongolica is an ecologically important grassland fungus that forms distinct fairy rings, which are hotspots of soil microbial activity. In this study, we investigated soil fungal communities across three spatial zones of L. mongolica fairy rings (inside, fruiting, and outside zones) in the Bayanbulak alpine grassland of Xinjiang, China. High-throughput sequencing, co-occurrence network analysis, and functional prediction tools (FUNGuild and PICRUSt2) were applied to assess community structure, interactions, and environmental drivers. The fruiting zone was dominated by L. mongolica, showing reduced fungal diversity, simplified microbial networks, and increased laccase activity, whereas the outside zone maintained higher diversity and more complex interactions. Redundancy analysis revealed strong correlations between fungal community composition and nitrogen availability, laccase activity, and pH. Functional predictions indicated spatially distinct trophic strategies, with saprotrophs enriched in the fruiting zone and ectomycorrhizal fungi dominant in other zones. These findings suggest that elevated laccase activity and nitrogen cycling may be key processes through which L. mongolica influences soil fungal zonation in grassland ecosystems.